(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To compare job strain and related factors among nurses at District 6 Medical Center and Tan Phu District Medical Center, Ho Chi Minh City, in 2025. Methods: An analytical cross-sectional study was conducted from December 2024 to December 2025 among 294 nurses working at the two medical centers. The Vietnamese version of the Job Content Questionnaire (JCQ-V) developed by Robert Karasek was used to assess job strain. Data were entered using Epidata 3.1 and analyzed with Stata 14.0. Results: The overall prevalence of high job strain among nurses was 6.1%; specifically, it was 5.4% at Tan Phu District Medical Center, lower than the 6.8% reported at District 6 Medical Center. Nurses at Tan Phu District Medical Center had a higher prevalence of high physical demand compared to those at District 6 Medical Center (60.5% vs. 44.9%), but received lower social support (76.8% vs. 85.1%). Factors significantly associated with high job strain included weekly working hours, holding concurrent positions, and caring for children under five years old. Conclusion: Nurses at District 6 Medical Center tended to experience higher job strain compared to nurses at Tan Phu District Medical Center.